Non-alcoholic fatty liver disease in a pediatric patient with heterozygous familial hypobetalipoproteinemia due to a novel APOB variant: a case report and systematic literature review - Molk, Neza; Bitenc, Mojca; Urlep, Darja; Zerjav Tansek, Mojca; Bertok, Sara; Trebusak Podkrajsek, Katarina; Sustar, Ursa; Kovac, Jernej; Battelino, Tadej; Debeljak, Marusa; Groselj, Urh (Frontiers in Medicine, 2023)
Background: Familial hypobetalipoproteinemia (FHBL) is an autosomal semi-dominant disorder usually caused by variants in the APOB gene that frequently interfere with protein length. Clinical manifestations include malabsorption, nonalcoholic fatty liver disease, low levels of lipid-soluble vitamins, and neurological, endocrine, and hematological dysfunction. Methods: Genomic DNA was isolated from blood samples of the pediatric patient with hypocholesterolemia, and his parents and brother. Next-generation sequencing (NGS) was performed, and an expanded dyslipidemia panel was employed for genetic analysis. Case report: Genetic investigation revealed the presence of a heterozygous variant in the APOB (NM_000384.3) gene c.6624dup[=], which changes the open reading frame and leads to early termination of translation into the p.Leu2209IlefsTer5 protein (NP_000375.3). The identified variant was not previously reported. Familial segregation analysis confirmed the variant in the mother of the subject, who also has a low level of low-density lipoprotein and non-alcoholic fatty liver disease. We have introduced therapy that includes limiting fats in the diet and adding lipid-soluble vitamins E, A, K, and D and calcium carbonate. We reported 35 individuals with APOB gene variations linked to FHBL in the systematic review. Conclusions: We have identified a novel pathogenic variant in the APOB gene causing FHBL in the pediatric patient with hypocholesterolemia and fatty liver disease. This case illustrates the importance of genetic testing for dyslipidemias in patients with significant decreases in plasma cholesterol as we can avoid damaging neurological and ophthalmological effects by sufficient vitamin supplementation and regular follow-ups.